Sex differences in frequency of instrumental activities of daily living after cardiac rehabilitation and its impact on long-term mortality in patients with heart failure. (3rd October 2022) - Nozaki, K; Hamazaki, N; Kamiya, K; Uchida, S; Noda, T; Maekawa, E; Matsunaga, A; Yamaoka-Tojo, M; Ako, J
Abstract: Introduction: While the major outcome of cardiac rehabilitation for heart failure (HF) is the improvement of exercise tolerance, prognosis, and quality of life, instrumental activities of daily living (IADL) has also been focused on as one of the its outcomes. IADL has been reported to be associated with all-cause mortality and quality of life in community-dwelling people and in patients with stable heart disease, but no report has examined the relationship between IADL after cardiac rehabilitation for HF and prognosis. In addition, it is assumed that sex differences may affect the frequency of performing each component of IADL, but there are no reports examining the association with prognosis by sex. Purpose: The present study aimed to investigate the sex differences in frequency of IADL and its impact on outcomes. Methods: We retrospectively studied 490 consecutive patients who were admitted due to acute decompensated HF and participated in outpatient cardiac rehabilitation after discharge. The study was performed in accordance with the tenets of the Declaration of Helsinki, and the protocol was approved by the Ethics Committee of our institution. IADL frequency was assessed using the questionnaire-based Frenchay Activities Index (FAI). The primary endpoint was all-cause death and secondary endpoint was combined events (all-cause death and/or readmission due to HF). We performed the Kaplan–Meier and log-rank tests and multivariable Cox regression analysis to evaluate the prognostic predictive capability of the FAI. Results: The study population had a median age of 69 (interquartile range [IQR]: 58–76) years, and 33.9% of patients were females. The median FAI score was 24 (IQR: 16–29) points. According to the Youden index based on the area under the curve calculated by the receiver operating characteristics curve, the cut-off values of FAI for all-cause death in all-over, females, and males were 23, 22, and 23 points, respectively. Over a median follow-up period of 4.8 years (IQR: 2.3–6.6 years), all-cause death and combined events were occurred in 95 (19.4%) and 213 (43.5%), respectively. After adjustment for several pre-existing prognostic factors, IADL assessed by the FAI was independently associated with all-cause mortality (hazard ratio [HR]: 0.961, 95% confidence interval [CI]:0.937–0.986) and combined events (HR: 0.968, 95% CI: 0.952–0.985), respectively. In addition, there was no interaction between sex in prognostic capability (P=0.664). Conclusion: Lower IADL frequency assessed by FAI at the end of outpatient cardiac rehabilitation was shown to be associated with poorer prognosis in patients with HF, regardless of sex. The IADL level is generally higher in females than in males but seems to be a useful marker for risk stratification at the end of cardiac rehabilitation in both females and males. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Grant-in-Aid [JSPS KAKENHI Grant Number JP 19K19884]